2004
DOI: 10.1111/j.1582-4934.2004.tb00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Double transgenic mice with Type 1 diabetes mellitus develop somatic, metabolic and vascular disorders

Abstract: The double transgenic mice (dTg) were obtained by mating: (i) transgenic mice expressing the hemagglutinin of influenza virus under the insulin promoter with (ii) transgenic mice expressing specific T lymphocytes with receptor for the immunodominant epitope of the same virus. In this study we show that dTg mice developed type 1 diabetes mellitus associated with hyperglycemia, low level of plasma insulin, glucosuria, weight loss and ~ 90% mortality (at 3 months biological age). The membrane of red blood cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These changes occurred in the range: ODH group > OD group > C group. Recently, in a double transgenic mice with Type 1 diabetes mellitus we reported that RBCs displayed an augmented sensitivity to the osmotic shock (compared to non-diabetic controls) assessing systemic oxidative stress [31]. The latter can be counterbalanced by the powerful antioxidant poten- tial of RBCs that act as mobile detoxifying units [32].…”
Section: Concentrationmentioning
confidence: 99%
“…These changes occurred in the range: ODH group > OD group > C group. Recently, in a double transgenic mice with Type 1 diabetes mellitus we reported that RBCs displayed an augmented sensitivity to the osmotic shock (compared to non-diabetic controls) assessing systemic oxidative stress [31]. The latter can be counterbalanced by the powerful antioxidant poten- tial of RBCs that act as mobile detoxifying units [32].…”
Section: Concentrationmentioning
confidence: 99%
“…Activation of STAT-3 and ERK1/2 correlate with the proliferative activities expressed by SMCs grown in high glucose concentrations. The intense proliferative activities of SMCs were observed also in vivo in the renal arteries of double transgenic mice with type 1 Diabetes mellitus; the cells displayed centriols within cytoplasm, a morphological evidence that assess cells proliferation (Radu et al, 2004).…”
Section: Smcs Molecules Affected By High Glucose Concentrationmentioning
confidence: 97%
“…The Ins-HA ± /TCR-HA ± double transgenic Balb/c mice (dTg) were obtained as previously described. 3,4 Briefly, the mice express simultaneously the hemagglutinin (HA) of influenza virus under the rat insulin promoter (Ins-HA) and T cell receptor (TCR) specific for the immunodominant CD4 T cell epitope of HA (HA110-120) in pancreatic β-cells. Since the Ins-HA +/+ Tg mice were homozygous and the TCR-HA ± Tg mice were heterozygous, the offspring were either Ins-HA ± /TCR-HA ± (dTg) mice (which developed diabetes) or Ins-HA ± /TCR-HA -/-(sTg) mice (which did not develop diabetes).…”
Section: Experimental Animal Modelsmentioning
confidence: 99%
“…week of age, develops gradually T1D with somatic, metabolic and vascular disorders comparable to human diabetes. [3][4][5] These characteristics allow the study of the etiopatogenic mechanisms of early diabetic nephropathy, the understanding of which could open up the possibility of finding new targets for the therapy of this disease.…”
mentioning
confidence: 99%